The Extent of Mathematics Teacher’s Awareness of Their Students’ Misconceptions in Learning Geometrical Concepts in the Intermediate Education Stage - Ahmad Al-Khateeb, Mohammad (European Scientific Journal, ESJ, 2016)
This study aims to examine and highlight the extent of mathematics teacher’s awareness of their student’s geometrical misconceptions and mistakes in the intermediate education stage. The sample consisted of (400) first grade students and (40) teachers. The results showed that intermediate education stage students suffered from various geometrical misconceptions such as parallelogram, trapezoid, rhombus, etc. Additionally, the study spotlighted mathematics teachers’ lack of awareness of their student’s mistakes due to their poor introductory techniques, inability to put suitable instructional plans to teach geometrical concepts and analyze them into their sub-components, incapability to use various instructional methods to teach such concepts, and other negative factors. The study proposed some recommendation to benefit from by all concerned parties in the teachinglearning process to overcome students’ geometrical misconceptions including educational planners, curricula authors, educational supervisors, and teachers. Finally, the study suggested some hints on future research in this field.